CONSUMER BEHAVIOR TOWARDS INTRODUCING 3G MOBILE IN PALESTINE: THE CASE OF BETHLEHEM GOVERNORATE - El-Jafari, Mahmoud; Yousef, Raneen; Jamoos, Ali (International Review of Management and Marketing, 2020)
This research focuses on the factors that influence customers’ behavior towards the introduction of 3G cellular data in Bethlehem Governorate, in the West Bank (WB), Palestine, which was introduced at the beginning of 2018. Therefore, the main purpose of this paper is about the examination of the factors that influence consumers’ usage of 3G cellular data. The research framework was based on the Theory of Planned Behavior (TPB) with the attitude, subjective norms, and perceived behavioral control factors. In addition to the extension of Technology Acceptance Model (TAM), the proposed model included the perceived usefulness and perceived ease of use factors. The perceived enjoyment factor was added to the model along with the TPB and TAM in order to examine the influence on the behavioral intention to use 3G cellular data. A simple random sampling strategy of a sample size of 402 3G’s customers from Bethlehem Governorate in the WB, Palestine was applied. Targeted respondents include who tried either currently using 3G services throughout a questionnaire that was constructed for this purpose. The data was analyzed by employing Structural Equation Modeling (SEM). The results indicate that perceived behavioral control, perceived enjoyment, and subjective norms are the influential factors. In contrast, perceived usefulness, perceived ease of use and attitude are not influencing the behavioral intention to use 3G mobile data services. Based upon the research findings, business implications, and limitations, further research was suggested were placed. Keywords: Theory of Planned Behavior, Technology Acceptance Model, 3G mobile data services, behavioral intention to use, perceived enjoyment. JEL Classifications: M31, M10 DOI: https://doi.org/10.32479/irmm.9119